Froth Flotation for Boehmite Recovery from a Water-Treatment Process Using Electrocoagulation - Elvin J. Guzmán-Jarquín; Roberto Pérez-Garibay; Francisco A. Acosta-González; Ramón Arellano-Piña (Metals)
Boehmite is an aluminum oxyhydroxide (AlO(OH)) and one of bauxite’s main mineral phases. This mineral is highly valued as an important source of aluminum for the metallurgical industry. However, the formation of synthetic boehmite has been observed in water treatment when aluminum anodes are used for electrocoagulation. This boehmite occurs in flocs that capture impurities from the water, but removing these flocs is a slow process. Therefore, the froth-flotation method was employed in the present study to float synthetic boehmite. This was achieved by evaluating the particle size of synthetic boehmite, generating microbubbles, and using an anionic collector system in a novel experimental setup. The results show that the surfactants sodium dodecyl sulfate (SDS) and potassium oleate (PO) favor the recovery of synthetic boehmite in different particle sizes, with the particle size favored related to the bubble size generated. It was noted that increasing the SDS concentration enabled the microbubbles to recover up to 95% of boehmite particles with diameters of less than 30 microns.